2017
DOI: 10.1002/sia.6261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold plasma process on the surface wettability of NBR and the kerosene resistance of NBR/PTFE composites

Abstract: In this study, first the acrylonitrile-butadiene rubber (NBR5080) was modified by argon (Ar), air, and oxygen plasma at low temperature, and the effect of plasma process (power, time, and pressure) on the surface properties of NBR5080, the interfacial properties, physical properties, and the mechanical properties of NBR5080/polytetrafluoroethylene (PTFE) composites were investigated. The state contact angle and the surface free energy were applied to characterize the surface wettability of NBR5080. The scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…After N 2 atmospheric plasma treatment, the contact angle decreased to 7.9°, indicating that the surface of this PDMS substrate was hydrophilic. Its contact angle increased from 7.9 to 55.9° after exposure to an atmospheric environment for 12 h, suggesting that the content of oxygen-containing functional groups on the plasma-treated surface of the PDMS substrate decreased upon increasing the exposure time . Therefore, the plasma treatment of the PDMS substrate subjected to thermal evaporation must be performed within 1 h to avoid such a decrease in the availability of oxygen-containing functional groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After N 2 atmospheric plasma treatment, the contact angle decreased to 7.9°, indicating that the surface of this PDMS substrate was hydrophilic. Its contact angle increased from 7.9 to 55.9° after exposure to an atmospheric environment for 12 h, suggesting that the content of oxygen-containing functional groups on the plasma-treated surface of the PDMS substrate decreased upon increasing the exposure time . Therefore, the plasma treatment of the PDMS substrate subjected to thermal evaporation must be performed within 1 h to avoid such a decrease in the availability of oxygen-containing functional groups.…”
Section: Resultsmentioning
confidence: 99%
“…Its contact angle increased from 7.9 to 55.9° after exposure to an atmospheric environment for 12 h, suggesting that the content of oxygen-containing functional groups on the plasma-treated surface of the PDMS substrate decreased upon increasing the exposure time. 58 Therefore, the plasma treatment of the PDMS substrate subjected to thermal evaporation must be performed within 1 h to avoid such a decrease in the availability of oxygen-containing functional groups. XPS revealed that the C 1s and O 1s peaks shifted after N 2 plasma treatment, indicating a strong connection between the Ag layer and PDMS ( Figure 1 c,d).…”
Section: Resultsmentioning
confidence: 99%
“…: łatwość przygotowania materiału do modyfikacji, dużą wszechstronność, kontrolę składu produktu, brak ograniczeń termodynamicznych, sterylność powierzchni w trakcie i po modyfikacji oraz możliwość osadzania różnych substancji na skalę komercyjną. Są tanie i nie wymagają użycia rozpuszczalników [13,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86].…”
Section: Powłoki Biobójczeunclassified
“…- fizyczną modyfikację powierzchni materiału -utworzenie powierzchni superhydrofobowej [77][78][79][80][81];…”
Section: Powłoki Biobójczeunclassified